THE SIGNIFICANCE OF PATHOMORPHOLOGICAL INVESTIGATION IN THE DIAGNOSIS OF PROSTATE TUBERCULOSIS - V. V. Potapov; E. V. Brizhatuk (Вестник урологии, 2018)
Introduction. Tuberculosis of the prostate is difficult for diagnosis, especially in the early stages.Material and methods. In an open prospective cohort study 84 patients with clinical and laboratory manifestations of chronic prostatitis were included.Purpose of the study. Тo estimate the most significant diagnostic criteria for prostate tuberculosis; role of prostate biopsy in differential diagnosis.Results. In 45 patients (53.6%) prostate tuberculosis was diagnosed, and in 39 patients (46.4%) chronic bacterial prostatitis was diagnosed. The diagnosis of prostate tuberculosis was confirmed microbiologically in 33.3% of patients, radiologically - in 24.4% of patients. A prostate biopsy followed by histological, bacteriological and molecular-genetic examination of the biopsy specimen confirmed the diagnosis in 20% of patients.Conclusion. The most informative in the differential diagnosis of tuberculosis and chronic prostatitis is the identification of M. tuberculosis; verification of diagnosis radiographically is possible only with the development of destruction of the parenchyma. The biopsy of the prostate should be examined not only pathologically, but also by molecular genetic methods.Disclosure: The study did not have sponsorship. The authors have declared no conflicts of interest.